The Concept of " Bodhipakkhiyā Dhammā " from the Perspective of Psychology and Self-Development - Supphadang, Anon; Ounephaivong , Somsak (BUDDHO, 2023)
Bodhipakkhiyā Dhammā a Buddhist principle, refers to the cultivation and development of the mind to achieve liberation from suffering, focusing on consistent and disciplined mental training. This paper explores the concept of " Bodhipakkhiyā Dhammā " through the lens of psychology and self-development. By connecting these principles with contemporary theories and practices for enhancing personal potential in the modern world, the psychological perspective emphasizes the development of emotions, thoughts, and behaviors through training and learning. Meanwhile, self-development is associated with continuous growth and reaching one’s highest potential. Additionally, the paper considers the significance of applying " Bodhipakkhiyā Dhammā " in daily life to reduce stress and foster sustainable happiness.